2020
DOI: 10.1371/journal.pone.0229693
|View full text |Cite
|
Sign up to set email alerts
|

Association between shift work and poor sleep quality in an Asian multi-ethnic working population: A cross-sectional study

Abstract: BackgroundWe aimed to examine the association between shift work and sleep quality in a diverse occupational type. MethodsThis was a cross-sectional study of self-reported sleep quality in 424 workers aged �21 using the Pittsburgh Sleep Quality Index (PSQI). We divided workers into two categories based on their PSQI score: (a) �5 (good sleep quality) and (b) >5 (poor sleep quality). We used multiple logistic regressions to assess the association between shift work and sleep quality adjusted for potential confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
(40 reference statements)
5
15
0
Order By: Relevance
“…The associations between work environment (high job demands, low job control, working an extra job, and shift work) and sleep disorders found among the Egyptian public officials agree with those in other nationalities (Ribet and Derriennic 1999;Kim et al 2018;Thach et al 2020). Shift work can disrupt the circadian rhythm.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The associations between work environment (high job demands, low job control, working an extra job, and shift work) and sleep disorders found among the Egyptian public officials agree with those in other nationalities (Ribet and Derriennic 1999;Kim et al 2018;Thach et al 2020). Shift work can disrupt the circadian rhythm.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, sleep disorders increased among highly educated women and decreased among highly educated men, which adds to the discrepant association between education level and sleep disorders. Sleep disorders were attributed to lower educational attainment in some studies (Thach et al 2020) and higher educational attainment in other studies (Yong et al 2017). Heo et al (2013) indicated both university or above-, and junior high schooleducated Koreans had significantly more sleep disorders than high school graduates.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on the work system, shift workers tend to have poorer sleep quality than the ones who do not. Shift workers were found to face 198% higher risks of poor sleep quality compared to non-shift workers (Thach et al, 2020). Although shift work can cause health problems, it is still used in various industries because of the production and service needs that must run for 24 hours.…”
Section: Discussionmentioning
confidence: 99%